Pengaruh Literasi Keuangan, Pomosi, dan Hedonisme terhadap Penggunaan Paylater pada Ibu Rumah Tangga di Kota Pontianak - Fitri, Urai Deby Tri; Mardiana, Mardiana (Universitas Batanghari Jambi, 2025)
This study aims to analyze the factors driving the use of PayLater services among housewives in Pontianak, with a focus on financial literacy, promotions, and hedonistic motivations. With the development of digital payment systems, PayLater services, which offer delayed payment options, have become increasingly popular among consumers. This study used a quantitative approach with a purposive sampling technique to survey 97 housewives in Pontianak. Data were collected through a questionnaire designed to measure financial literacy, the influence of promotions, hedonism, and the use of PayLater services using multiple linear regression analysis. The results show that financial literacy, promotions, and hedonism have a significant influence on the decision to use PayLater services, with promotions and hedonism having a stronger influence than financial literacy. Special offers such as discounts and cashback encourage usage, while the hedonistic desire for immediate gratification and consumption also plays a significant role.